2021
DOI: 10.1155/2021/6649412
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Immune Gene Expression Subtypes Reveals Osteosarcoma Immune Heterogeneity

Abstract: Background. Osteosarcoma (OS) patients have a poor response to immunotherapy due to the sheer complexity of the immune system and the nuances of the tumor-immune microenvironment. Methodology. To gain insights into the immune heterogeneity of OS, we identified robust clusters of patients based on the immune gene expression profiles of OS patients in the TARGET database and assessed their reproducibility in an independent cohort collected from the GEO database. The association of comprehensive molecular charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However, there are studies that have reported opposing findings with regard to the effects of tumor-infiltrating lymphocytes on neoadjuvant chemotherapy responses or prognosis [ 34 ]. This opposing finding could be because tumor-infiltrating lymphocytes are heterogeneous populations [ 35 , 36 ]. The TME heterogeneity affects various responses to clinical therapy; therefore, the TME is a potential biomarker for predicting clinical treatment effects and for screening tumor patients that can benefit from treatment, thereby informing clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are studies that have reported opposing findings with regard to the effects of tumor-infiltrating lymphocytes on neoadjuvant chemotherapy responses or prognosis [ 34 ]. This opposing finding could be because tumor-infiltrating lymphocytes are heterogeneous populations [ 35 , 36 ]. The TME heterogeneity affects various responses to clinical therapy; therefore, the TME is a potential biomarker for predicting clinical treatment effects and for screening tumor patients that can benefit from treatment, thereby informing clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, a small part of patients still received a poor survival outcomes [ 21 , 22 ]. With the in-depth recognition of TIME, the differential tumor microenvironment has been confirmed to play an important role in the poor survival outcomes of tumors [ 23 , 24 ]. Therefore, the exploration of TIME is a chance for improving therapeutic effect and prognosis in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, evidence has shown that the body's immune system may be in a constant battle with osteosarcoma cells including three stages: immune clearance, balance, and escape [11][12][13] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%